Formulasi Minuman Probiotik Kombinasi Sari Buah Mangga (Mangifera indica L.) dan Nanas (Ananas comosus L.) dengan Penambahan Susu Skim dan Bakteri Asam Laktat - Fadliah, Lia; Kasrawati, Kasrawati; Riska Vatica, Jeny; Muazzinah, Muazzinah; Azzuhra, Nurul (KENANGA : Journal of Biological Sciences and Applied Biology, 2026)
Digestive tract disorders such as diarrhea, gastritis, constipation, and Irritable Bowel Syndrome (IBS) are common health problems among the Indonesian population. Probiotics are known to play an important role in maintaining the balance of intestinal microbiota, inhibiting the growth of pathogenic bacteria, and enhancing immune responses. Mango (Mangifera indica L.) and pineapple (Ananas comosus L.) contain vitamins, dietary fiber, antioxidants, and natural prebiotic compounds that support the growth of lactic acid bacteria (LAB). The addition of skim milk serves as an additional nutrient source for LAB to optimize the fermentation process. This study aimed to formulate a probiotic beverage based on a combination of mango and pineapple juices with the addition of skim milk and lactic acid bacteria, as well as to evaluate the total LAB count, lactic acid content, and vitamin C content. This research employed a laboratory experimental method using a post-test only group design. The treatments consisted of skim milk concentrations of 1%, 2%, and 3%, with the addition of 10% LAB starter culture. The evaluation included LAB enumeration using the Total Plate Count method, determination of lactic acid content by titration with 0.1 N NaOH, and vitamin C analysis using the iodimetric titration method. The results showed that the formulation containing 1% skim milk produced the highest LAB count, reaching 1.8 × 10¹⁰ CFU/mL. The lactic acid content ranged from 0.45% to 2.07%, with formulations containing 2% and 3% skim milk meeting the Indonesian National Standard (BSN) requirements (0.5–2.0%). The average vitamin C content was 0,056%, which was considerably higher than the standard range specified by SNI (0.01–0.1%). It can be concluded that the combination of mango and pineapple juices with skim milk has the potential to be formulated as a probiotic beverage that meets quality standards. Formulations containing 2% and 3% skim milk exhibited the best physicochemical characteristics, while the 1% skim milk formulation resulted in the highest LAB count. Keywords: probiotic beverage; mango juice; pineapple; skim milk; vitamin C; lactic acid bacteria.